1996
DOI: 10.1021/bp9600593
|View full text |Cite
|
Sign up to set email alerts
|

Polylinker-Encoded Peptides Can Confer Toxicity to Recombinant Proteins Produced in Escherichia coli

Abstract: Three DNA segments encoding fragments of the p60 capsid protein of rabbit haemorrhagic disease virus (RHDV) have been cloned and expressed in Escherichia coli. The cDNAs were placed under the control of the T7 promoter in a pET-derived expression vector designed to produce C-terminal histidine tail fusions. By using different cloning strategies, cell toxicity exhibited by some of the expressed products was dramatically affected, coincident with minor modifications in the carboxy terminus sequences of the recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Since no significant differences between growth of cultures producing LAC10, LAC110 and LAC174 were detected, we can argue that there might be other factors, different from molecular mass, affecting growth of MC1061/pJLACVP1 cells. In fact, some specific amino acid sequences are known to cause toxicity on the producing cells (Couto and Friedberg, 1989;Tsai et al, 1989;Viaplana and Villaverde, 1996). Production of complete, unfused VP1 protein was reported to induce severe symptoms of plasmid instability and toxicity, even under non-inducing conditions (Vidal et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Since no significant differences between growth of cultures producing LAC10, LAC110 and LAC174 were detected, we can argue that there might be other factors, different from molecular mass, affecting growth of MC1061/pJLACVP1 cells. In fact, some specific amino acid sequences are known to cause toxicity on the producing cells (Couto and Friedberg, 1989;Tsai et al, 1989;Viaplana and Villaverde, 1996). Production of complete, unfused VP1 protein was reported to induce severe symptoms of plasmid instability and toxicity, even under non-inducing conditions (Vidal et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The production of a recombinant protein can result in a variety of cellular stress responses, which can be reflected by reduced growth rates (e.g., Viaplana and Villaverde, 1996), ribosome destruction (Dong et al, 1995), stress protein synthesis (e.g., Hoffmann and Rinas, 2000;Parsell and Sauer, 1989;Ramirez and Bentley, 1993), and alterations of central carbon metabolism (e.g., George et al, 1992). For quantitative evaluation of the metabolic perturbation, the analysis of metabolic fluxes has emerged as an important tool in the field of metabolic engineering (Vallino and Stephanopoulos, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Although the genetics and physiology of E. coli are well characterized, the cellular mechanism of the cell damage caused by heterologous proteins remains unclear. To date, it has been reported that a strong SOS response is induced with the expression of diverse heterologous proteins, including enzymes and nonenzymatic proteins/ peptides (Aris et al, 1998;Bedouelle et al, 1990;Benito et al, 1995;Laity et al, 1993;Pham and Coleman, 1985;Sisk et al, 1992;Viaplana and Villaverde, 1996;Vidal et al, 1991;Colasanti and Denhardt, 1985). From the fact that the SOS response is induced irrespective of the biological function of the expressed recombinant proteins, Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the observed SOS response could be related to either the metabolic burden or the toxicity associated with the production of recombinant proteins. For other products, the presence of particular amino acid sequences could be responsible for their toxicity (Sisk et al, 1992;Viaplana and Villaverde, 1996;Vidal et al, 1991), and their removal rendered nontoxic products and increased the yield (Sisk et al, 1992;Vidal et al, 1991). It seems that the SOS response is induced in recombinant E. coli regardless of the biological properties of synthesized foreign proteins/peptides; the reason why the SOS-inducing events happen along with recombinant gene expression still remains unclear.…”
Section: Introductionmentioning
confidence: 99%